2019
DOI: 10.3389/fnins.2019.01031
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Pituitary Adenylate Cyclase Activating Polypeptide in Retinal Degenerations of Metabolic Origin

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP1-38) is a highly conserved member of the secretin/glucagon/VIP family. The repressive effect of PACAP1-38 on the apoptotic machinery has been an area of active research conferring a significant neuroprotective potential onto this peptide. A remarkable number of studies suggest its importance in the etiology of neurodegenerative disorders, particularly in relation to retinal metabolic disorders. In our review, we provide short descriptions of various pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Furthermore, the PLC and AC/cAMP signaling pathway could mediate downstream targets, such as ras-associated protein-1 (RAP1)[ 34 ], MAPKs [ 35 - 38 ], NF-kB [ 39 , 40 ], janus kinase (JAK) [ 41 , 42 ], cJun [ 43 , 44 ], and phosphatidylinositol 3-kinase (PI3K) [ 45 ]. In parallel with the PLC and AC/cAMP pathway, these downstream signaling pathways may also be directly activated by PAC1 in some cells [ 29 , 46 , 47 ] ( Fig. 1 ).…”
Section: Pacap and Receptorsmentioning
confidence: 99%
“…Furthermore, the PLC and AC/cAMP signaling pathway could mediate downstream targets, such as ras-associated protein-1 (RAP1)[ 34 ], MAPKs [ 35 - 38 ], NF-kB [ 39 , 40 ], janus kinase (JAK) [ 41 , 42 ], cJun [ 43 , 44 ], and phosphatidylinositol 3-kinase (PI3K) [ 45 ]. In parallel with the PLC and AC/cAMP pathway, these downstream signaling pathways may also be directly activated by PAC1 in some cells [ 29 , 46 , 47 ] ( Fig. 1 ).…”
Section: Pacap and Receptorsmentioning
confidence: 99%
“…Neuropeptides have an essential role in retinal physiology, as they affect information processing through multiple retinal peptidergic pathways [ 4 , 5 , 6 ]. The neuropeptides somatostatin (SST) and pituitary adenylate cyclase-activating polypeptide (PACAP) have various effects in many retinal physiological and pathological conditions [ 5 , 7 , 8 , 9 ]. These two neuromodulators share similarities in their functional relevance and structural parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Age-related retinal functional and structural changes in the retina are well described in the aging human population worldwide. Neuropeptides and/or their analogs could offer an opportunity for treatments in certain retinal pathological conditions [ 7 , 29 ]. Previous studies have described that endogenous PACAP deficiency accelerated age-related retinal degeneration [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects tear secretion (Nakamachi et al 2016), influences muscle responses of the iris (Yamaji et al 2005), increases blood flow in the eye (Dorner et al 1998) and regulates pigment epithelial cell functions (Fabian et al 2012(Fabian et al , 2019Maugeri et al 2019a). Most importantly, as a general protective peptide found not only in the central nervous system but several peripheral organs as well (Laszlo et al 2019;Liu et al 2019;Polanco and Pennuto 2018;Reglodi et al 2018d, e;Shioda et al 2019;Szegeczki et al 2019), PACAP has been shown to exert diverse retinoprotective effects in models of toxic, ischemic, inflammatory and traumatic retinal injuries (Atlasz et al 2016(Atlasz et al , 2019Cheng et al 2018;Endo et al 2011;Gabriel et al 2019;Kvarik et al 2016;Seki et al 2008;Szabadfi et al 2016;Vaczy et al 2016;Ye et al 2019a, b). Several retinal cell types can be protected by PACAP, including ganglion cells, bipolar neurons, amacrine and pigment epithelial cells (Atlasz et al 2008;Fabian et al 2019;Maugeri et al 2019a;Szabadfi et al 2012).…”
Section: Introductionmentioning
confidence: 99%